IMPLEMENTASI PERKEMBANGAN KECERDASAN SPIRITUAL PADA ANAK USIA DINI MELALUI KEGIATAN PEDULI SOSIAL DI LINGKUNGAN MASYARAKAT - Siti Masruroh; Mitra Sasmitra; Lusiana Rahmatiani; Rahma Dilla Zainuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Spiritual intelligence is an individual's ability to understand and internalise spiritual values as a foundation in living life. In early childhood, the development of spiritual intelligence can be built through real experiences involving social care activities in the community. This study aims to examine the implementation of social care activities in supporting the development of spiritual intelligence in early childhood. The research method used is a qualitative approach with a case study of an early childhood education institution that implements a social activity-based programme. Data were collected through observation, interviews and documentation. The results showed that social care activities, such as sharing food, helping neighbours and environmental activities, can increase children's sense of empathy, responsibility and understanding of religious and human values. In addition, the involvement of parents and the community plays an important role in creating an environment that supports the development of children's spiritual intelligence. The conclusion of this study emphasises the importance of synergy between families, schools and communities in designing meaningful social activities for young children.